Assessment of the correlation between KAP scores regarding sugar-sweetened beverage consumption and hyperuricemia amongst Chinese young adults - Yun Zhang; Hong Di; Juan Wu; Xiaoxue Wang; Xinxin Han; Bingqing Zhang; Xuejun Zeng (BMC Public Health, 2024)
Abstract Background The prevalence of hyperuricemia in China has been consistently increasing, particularly among the younger generation. The excessive consumption of sugar-sweetened beverages is associated with hyperuricemia. This study examined the knowledge, attitudes, and practices (KAP) of Chinese young adults regarding sugar-sweetened beverage consumption and the correlation with hyperuricemia. Methods This cross-sectional investigation was conducted from June 28th, 2023, to July 21st, 2023, and enrolled Chinese young adults. Demographics and KAP were evaluated using a questionnaire (Cronbach’s α = 0.787). Factors influencing KAP scores were analyzed using multivariable analyses. Results A total of 1288 valid questionnaires were analyzed. The median knowledge, attitude, and practice scores were 16 (12,19)/22, 22 (20,24)/30, and 27.5 (23,31.75)/40. The multivariable analysis showed that bachelor’s/associate education (OR = 1.912, 95%CI: 1.128–3.239), white collar/employee (OR = 0.147, 95%CI: 0.105–0.206), educator (OR = 0.300, 95%CI: 0.174–0.518), healthcare worker (OR = 0.277, 95%CI: 0.188–0.407), not suffering from hyperuricemia (OR = 0.386, 95%CI: 0.253–0.590), and not having gout (OR = 0.456, 95%CI: 0.282–0.736) were independently associated with knowledge. Age 26–30 (OR = 1.470, 95%CI: 1.052–2.052), age 31–35 (OR = 1.489, 95%CI: 1.097–2.022), age 36–40 (OR = 0.328, 95%CI: 1.010–1.746), age 41–44 (OR = 1.548, 95%CI: 1.091–2.198), and not having hyperuricemia (OR = 0.512, 95%CI: 0.345–0.760) were independently associated with attitude. White collar/employee (OR = 0.386, 95%CI: 0.285–0.521), educator (OR = 0.534, 95%CI: 0.317–0.899), healthcare worker (OR = 0.341, 95%CI: 0.236–0.493), having siblings (OR = 0.725, 95%CI: 0.573–0.917), and not suffering from hyperuricemia (OR = 0.442, 95%CI: 0.296–0.659), were independently associated with practice. Conclusion Chinese young adults display moderate KAP toward sugar-sweetened beverages. Notably, an association was observed between hyperuricemia and each KAP dimension.